Order effects in the recall of autobiographical memories: evidence for an organisation along temporal and emotional features. Issue 3 (16th March 2021) - Nusser, Lisa; Zimprich, Daniel
ABSTRACT: Investigating the recall process of autobiographical memories (AMs) and, particularly, the order in which AMs are recalled has the potential to shed light on the organisation of autobiographical memory. However, research on order effects in the recall of AMs is relatively rare. Moreover, to date, no study addressed the question of where emotion fits into the organisation. The present study aimed to close this gap by examining whether emotional valence serves as one organising principle. Data come from 117 older adults ( M  = 74.11; SD = 7.06) who reported up to 39 AMs. The use of a multivariate multilevel model with autoregressive effects allows us to analyse the order effect within one person, as well as how the order effect differs between persons. The results replicated a temporal first-order effect that has been shown in previous studies and moreover, demonstrated a temporal second-order effect. Furthermore, our results indicated an emotional first-order effect that was even stronger than the temporal first-order effect and an emotional second-order effect. In addition, both first-order effects differed reliably between persons. Thus, the present study emphasises the need for considering emotion in current theoretical formulations of autobiographical memory and also of considering individual differences in the order of AMs recalled.